2011
DOI: 10.2967/jnmt.110.081265
|View full text |Cite
|
Sign up to set email alerts
|

Could Different Hydration Protocols Affect the Quality of 18F-FDG PET/CT Images?

Abstract: In a group of oncologic patients undergoing 18 F-FDG PET/CT, we compared 4 different protocols of hydration to investigate their impact on image quality and to choose the best practice. Methods: One hundred twenty subjects undergoing 18 F-FDG PET/CT were randomized into 4 groups: group A, receiving free oral hydration; group B, receiving an intravenous injection of 10 mg of furosemide and infusion of 500 mL of saline solution starting 5 min after tracer injection; group C, receiving oral hydration with 500 mL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
(19 reference statements)
1
9
0
Order By: Relevance
“…They provided medical history, completed the International Physical Activity Questionnaire (IPAQ) and underwent measurements for anthropometry, blood pressure and plasma glucose using standard methods . Subsequently, we administered intravenously 5 mg of diazepam (stedon) to avoid excessive muscle activity during the examination and 40 mg of furosemide (lasix) to reduce excretory system activity in participants with systolic blood pressure >110 mmHg . Thereafter, we administered 358 ± 21·9 mega Becquerel of 18 F‐FDG intravenously according to each participant's body weight following standard methodology .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They provided medical history, completed the International Physical Activity Questionnaire (IPAQ) and underwent measurements for anthropometry, blood pressure and plasma glucose using standard methods . Subsequently, we administered intravenously 5 mg of diazepam (stedon) to avoid excessive muscle activity during the examination and 40 mg of furosemide (lasix) to reduce excretory system activity in participants with systolic blood pressure >110 mmHg . Thereafter, we administered 358 ± 21·9 mega Becquerel of 18 F‐FDG intravenously according to each participant's body weight following standard methodology .…”
Section: Methodsmentioning
confidence: 99%
“…12 Subsequently, we administered intravenously 5 mg of diazepam (stedon) to avoid excessive muscle activity during the examination 13 and 40 mg of furosemide (lasix) to reduce excretory system activity in participants with systolic blood pressure >110 mmHg. 14 Thereafter, we administered 358 AE 21Á9 mega Becquerel of 18 F-FDG intravenously according to each participant's body weight following standard methodology. 15 Finally, we performed the PET/CT examination 1 h thereafter.…”
Section: Experimental Designmentioning
confidence: 99%
“…Also, the effects of furosemide and butylscopolamine could not be investigated. However, research on adults has demonstrated that furosemide effectively eliminates 18 F-FDG activity from the lower urinary tract and thus improves the diagnostic accuracy in abdominopelvic malignancies [39]; interestingly, furosemide was shown to not substantially affect tracer distribution within the mediastinal blood pool and soft tissues, respectively [40]. Butylscopolamine, on the other hand, reduces artefacts coming from bowel peristalsis, thus also improving the accuracy of abdominal 18 F-FDG PET reporting [41].…”
Section: Discussionmentioning
confidence: 99%
“…This points to the necessity of implementing several protocols for patient preparation, which can signifi cantly improve the detection rate of primary bladder malignancy [5][6][7].…”
Section: Discussionmentioning
confidence: 99%